2014
DOI: 10.1186/s40199-014-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of gonadotropin-releasing hormone agonist versus gonadotropin-releasing hormone antagonist in Iranian infertile couples: oocyte gene expression

Abstract: BackgroundThe main objective of the present work was to compare the effects of the gonadotropin-releasing hormone agonist (GnRH-a) and GnRH antagonist (GnRH-ant) on the gene expression profiles of oocytes obtained from Iranian infertile couples undergoing in vitro fertilization (IVF).MethodsFifty infertile couples who underwent IVF between June 2012 and November 2013 at the Infertility Center of Tehran Women General Hospital, Tehran University of Medical Sciences, were included in this study. We included women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Although the mean number of oocytes retrieved was higher in the agonist group compared to the antagonist group, there was a trend for higher pregnancy rates and number of embryos in the antagonist group compared to the agonist group in low AMH group. In a recent study, Hoseini et al (2014) showed that the expression levels of some genes involved in the cytoplasmic maturity, antiapoptotic process and adenosine triphosphate production were higher in human oocytes of the women in the GnRH-ant protocol versus those of the women in the GnRH-a protocol (43). For these reasons, antagonist protocol may have a positive influence on both oocyte and embryo quality; consequently, increase the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mean number of oocytes retrieved was higher in the agonist group compared to the antagonist group, there was a trend for higher pregnancy rates and number of embryos in the antagonist group compared to the agonist group in low AMH group. In a recent study, Hoseini et al (2014) showed that the expression levels of some genes involved in the cytoplasmic maturity, antiapoptotic process and adenosine triphosphate production were higher in human oocytes of the women in the GnRH-ant protocol versus those of the women in the GnRH-a protocol (43). For these reasons, antagonist protocol may have a positive influence on both oocyte and embryo quality; consequently, increase the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…An important part of reproductive medicine in infertility treatment is ovarian stimulation by drugs to gain a higher number of mature oocyte retrieved for the purpose of increasing pregnancy rates in comparison with the normal cycles (1). Recently, drug usage has been founded to make final oocyte maturation in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was accompanied by an increase in the incidence of ovarian hyperstimulation syndrome (OHSS) and canceled cycles ( 17 , 32 ). In contrast to these results, the molecular studies on the oocytes, obtained through the antagonist protocol in patients with high AMH levels, indicated that the gene expressions of ATPase and BMP15 , as two indicators of oocyte quality, enhanced through the antagonist protocol ( 4 ). Therefore, the antagonist protocol can be the more desirable option in high AMH cases.…”
Section: Discussionmentioning
confidence: 71%
“…Although the two common ovarian stimulation protocols (GnRH agonist and GnRH antagonist) exhibit similar implantation and pregnancy rates, each protocol entails specific characteristics. In fact, the agonist protocol leads to higher number of oocytes per cycle, whereas the antagonist protocol curtails the gonadotropin dose, shortening the stimulation period and saving the treatment costs, which in turn leads to patient comfort ( 1 - 4 ).…”
Section: Introductionmentioning
confidence: 99%